Can Couple Level Attachment Mediate the Influence of Depressive Symptoms on Health?. Issue 2 (14th March 2016) - Sandberg, Jonathan G.; Novak, Joshua R.; Bates, Tasha
ABSTRACT: This study examined whether couple attachment behaviors, as measured by the BARE (Brief Accessibility, Responsiveness, and Engagement Scale), can mediate the influence of depressive symptoms on health for men and women. Data were gathered from the Relate Institute (www.relateinstitute.com ) from 797 couples who were in a romantic relationship. Results showed depressive symptoms negatively predict daily eating habits and activity level and positively predicted total health problems and healthcare utilization for both females and males. For partners, female depression negatively predicated both male physical activity and total health problems, and also positively predicted healthcare utilization for men. Results also suggest that attachment behaviors mediated the association between depressive symptoms and total health problems. Findings are discussed from both a clinical and systemic perspective. It may be that fostering secure attachment behaviors in romantic relationships would be a helpful tool for providers working to address the depressive symptoms patients face.